Mining heritage and revalorization underground structures - Gayko, Gennadiy; Biletsky, Volodymyr (Skhid, 2016)
In the article the analysis of historical sources, the current state, problems and prospects revalorization of old buildings and underground mining sites in the world and in Ukraine. Examples of successful projects revalorization of old mining sites and create underground tourist trails. Formulated tasks for humanitarian and engineering areas on museification old mines and underground construction sites. There is a problem of disparity of mineral resources major role in society and lack of attention to the information environment. There is great public interest modern and old mining industrial regions in preserving the historical heritage of old miners and underground structures. This requires systematic steps to save a few different times mining monuments that have survived. Methods and revalorization museification such facilities require a combination of humanitarian and engineering knowledge, including geoconstruction technology and global experience preserve these objects. In Ukraine, the preservation of industrial heritage by museification underground facilities is only some few attempts. There are interesting and promising projects that could be underground museum and tourist routes. They have the potential to promote technical knowledge. Musefication mining buildings - part of school and vocational higher education. Based on the possible establishment of mining museums in teaching and research centers. They contribute to the development of higher education institutions, domestic and international scientific tourism, promoting national brands in the world. It is important that played industrial and urban monuments and museum exhibitions not only give an opportunity to get acquainted with the world of old buildings and technologies, but also revealed the inner spiritual world, traditions and cultural heritage of the ancient conquerors of underground space, carrying the best spiritual progress in the future.